Communicating partners : 30 years of building responsive relationships with late-talking children including autism, Asperger's syndrome (ASD), Down syndrome, and typical development developmental guides for professionals and parents - MacDonald, James D. (James David), 1940- (Jessica Kingsley Publishers, 2004)
Communicating Partners, the result of over thirty years of clinical practice and research work with pre-verbal and verbal children with language delays, offers an innovative approach to working with late talking children that focuses on developing relationships through mutual understanding. Providing detailed maps of what children and their life partners need to do to ensure effective social relationships, the program focuses on five key stages of communication development - interactive play, nonverbal communication, social language, conversation, and civil behavior - and five life-long respon.